2014
DOI: 10.1039/c4cp00496e
|View full text |Cite
|
Sign up to set email alerts
|

Highly durable fuel cell electrodes based on ionomers dispersed in glycerol

Abstract: A major, unprecedented improvement in the durability of polymer electrolyte membrane fuel cells is obtained by tuning the properties of the interface between the catalyst and the ionomer by choosing the appropriate dispersing medium. While a fuel cell cathode prepared from aqueous dispersion showed 90 mV loss at 0.8 A cm(-2) after 30,000 potential cycles (0.6-1.0 V), a fuel cell cathode prepared from glycerol dispersion exhibited only 20 mV loss after 70,000 cycles. This minimum performance loss occurs even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 19 publications
2
68
0
Order By: Relevance
“…While ECSA measurement only requires electron and proton access, good access to reactant O 2 is also required for ORR. Minor changes in the ionomer distribution in the electrode have been shown to significantly affect the ORR activity as well as fuel cell performance at high current density, 3,35,[37][38][39][40][41][42] a topic of great interest in the fuel cell community. 3,43,44 Therefore, it is not a surprise that these vastly diverse methods yield slightly different performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While ECSA measurement only requires electron and proton access, good access to reactant O 2 is also required for ORR. Minor changes in the ionomer distribution in the electrode have been shown to significantly affect the ORR activity as well as fuel cell performance at high current density, 3,35,[37][38][39][40][41][42] a topic of great interest in the fuel cell community. 3,43,44 Therefore, it is not a surprise that these vastly diverse methods yield slightly different performance.…”
Section: Resultsmentioning
confidence: 99%
“…37 These so-called mudcracks can cause premature failure of membrane and electrodes. The mudcracks are generally formed due to surface-tension stress generated during the ink drying.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural differences between LSC and SSC PFSA have been studied by Kreuer et al 14 They reported that SSC PFSA does not have any distinct differences in water and proton transport, yet provides better thermomechanical stability, which is anticipated due to the stability of the electrolyte/electrode interface. The effect of different catalyst dispersing solvents for electrode preparation has been also studied by Kim et al 15 The electrodes prepared from water-isopropanol solvent showed numerous large scale open cracks (>100 μm) while the electrodes prepared from glycerol and N-methyl pyrrolidone (NMP) exhibited distributed microcracks (<10 μm) and a crack-free structure, respectively. Based on this information, a series of MEAs having different cathode structures were fabricated and the stability of Nafion 212 membrane was examined by measuring the H 2 crossover rate during a 200-hour OCV accelerated stress test (AST).…”
Section: +mentioning
confidence: 99%
“…The effect of different catalyst dispersing solvents for electrode preparation has been also studied by Kim et al 15 The electrodes prepared from water-isopropanol solvent showed numerous large scale open cracks (>100 μm) while the electrodes prepared from glycerol and N-methyl pyrrolidone (NMP) exhibited distributed microcracks (<10 μm) and a crack-free structure, respectively. Based on this information, a series of MEAs having different cathode structures were fabricated and the stability of Nafion 212 membrane was examined by measuring the H 2 crossover rate during a 200-hour OCV accelerated stress test (AST).…”
mentioning
confidence: 99%